Development of Problem-Based Learning Practicum Modules for the Dangerous Goods Course - Dwi Candra Yuniar; Herlina Febiyanti; Shabrina Ramadhani; R.R. Retno Sawitri Wulandari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The Dangerous Goods course is a compulsory course followed by cadets of the Diploma 3 Airport Management study program. Providing Dangerous Goods material aims to discover how to handle and pack dangerous goods under predetermined regulations, not to endanger flight safety and security. However, the cadets felt that the Dangerous Goods course was challenging due to the lack of modules and difficulty understanding the very thick Dangerous Goods book. Problem-based learning used in this study was chosen because this learning model trains the Critical Thinking skills possessed by cadets under the Dangerous Goods course material, which requires a lot of practice. This research method uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research and development approach, which is a research method used to produce specific products and test the effectiveness of these products. The subjects of this study were 48 cadets of Palembang Aviation Polytechnic cadets who managed the airport. Researchers conduct research first to collect the data needed, then system development is carried out, and the system is tested and evaluated. This study showed that the results of media expert validation were obtained by 90.% with valid categories and material expert validation results by 91.% with valid categories. Based on the validity and product effectiveness results, problem-based learning e-modules on the developed Dangerous Goods material are valid and effectively used by teachers and students in the learning process.